2022
DOI: 10.3390/medicina58070894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endodontic Failures between Nonsurgical Retreatment and Endodontic Surgery: Systematic Review and Meta-Analysis with Trial Sequential Analysis

Abstract: Background and Objectives: In the presence of a persistent endodontic lesion or endodontic failure, the alternative for the recovery of the dental element is endodontic retreatment or endodontic surgery, which consists in the surgical removal of the root apices with retrograde closure of the endodontium. The objective of this systematic review and meta-analysis was to provide an updated value of the Risk Ratio between the two types of treatment in order to offer to clinicians who propose a non-surgical endodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
(75 reference statements)
1
9
0
1
Order By: Relevance
“…Our finding of better outcome after microsurgery compared with non‐surgical retreatment is consistent with other reports (Bucchi et al, 2022; Dioguardi et al, 2022; Torabinejad et al, 2009), including tooth survival studies (Haxhia et al, 2021). Some studies have described faster healing after the surgical procedure compared with non‐surgical retreatment after 1 year, but a regression of successful cases for endodontic surgery over a follow‐up period of 4 years (Del Fabbro et al, 2007; Kvist & Reit, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of better outcome after microsurgery compared with non‐surgical retreatment is consistent with other reports (Bucchi et al, 2022; Dioguardi et al, 2022; Torabinejad et al, 2009), including tooth survival studies (Haxhia et al, 2021). Some studies have described faster healing after the surgical procedure compared with non‐surgical retreatment after 1 year, but a regression of successful cases for endodontic surgery over a follow‐up period of 4 years (Del Fabbro et al, 2007; Kvist & Reit, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Data results from meta-analyses report an aggregate risk ratio (RR) between nonsurgical endodontic retreatment and surgical endodontic retreatment of: 1.05 [0.74, 1.47] at one-year follow-up; RR 2.22 [1.45, 3.41] at two years of followup; an RR 1.08 [0.73 1.62] for a follow-up period of 3-4 years; and an RR 0.92 [0.53, 1.61] for a follow-up period of 8 to 10 years. The results of the present meta-analysis showed that, in the long term, the risk of failure is identical for both groups, with only a slightly higher risk of failure for non-surgical endodontic retreatments, when only two years of follow-up are considered [3].…”
Section: Resultsmentioning
confidence: 56%
“…In the presence of persistent endodontic lesions or endodontic failure, the alternative for the recovery of the dental element is endodontic retreatment or endodontic surgery, which consists of surgical removal of the root apices with retrograde closure of the endodontic [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root canal retreatment is a common procedure used to treat teeth that have failed previous root canal treatment. [17]. The goal of retreatment is to remove the old lling material, disinfect the root canals, and then ll them with a new material [ 30].…”
Section: Introductionmentioning
confidence: 99%